KONTRIBUSI CARA BELAJAR TERHADAP HASIL BELAJAR PENGOLAHAN DAN PENYAJIAN MAKANAN KONTINENTAL SISWA PROGRAM KEAHLIAN JASA BOGA SMKN 2 BUKITTINGGI - Zaimel, Yossy; Yulastri, Asmar; Faridah, Anni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to analyze the contribution of learning to the learning outcomes Continental Food Processing and Presentation of student membership food service program SMKN 2 Bukittinggi. This type of research is quantitative descriptive by using the correlation method. The subjects of this research were students of class XI SMKN 2 Bukittinggi, amounted to 70 people. Collecting data through direct observation and measurement using a questionnaire with Likert Scale. Hypothesis testing using correlation coefficient analysis. Based on the results of research shows that learning PPMK of food service student SMKN 2 Bukittinggi in both categories with a percentage of 70% and the learning outcomes in categories with a percentage 54.3%, with a correlation coefficient of 0.27. the hypothesis proposed (Ha) recieved, which reads some positive contribution and significant between learning styles to student learning outcomes Continental Food Processing and Presentation of SMKN 2 Bukittinggi.Kata Kunci: Learning, Learning Outcomes, Continental Food Processing and Presentation